Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1149/1.3466984
|View full text |Cite
|
Sign up to set email alerts
|

Quick Determination of Copper-Metallization Long-Term Impact on Silicon Solar Cells

Abstract: In this paper, we present a method to quickly evaluate the long-term effects of copper-containing metal stack systems for silicon solar cell front–side metallization. Copper diffusion, which is detrimental for the solar cell performance, is accelerated by exposing the cell to thermal stress. In this paper, we suggest to quantify the degree of copper diffusion into the cell by the very fast Suns- VOC technique, measuring the pseudo fill factor (pFF). Using three or more different temperatures, and assuming a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 6 publications
(6 reference statements)
1
44
0
Order By: Relevance
“…The annealing was to stress the performance of the cell in an effort to evaluate the long-term reliability of the solar cell with metallization. 27 A moderately high temperature of 200…”
Section: Resultsmentioning
confidence: 99%
“…The annealing was to stress the performance of the cell in an effort to evaluate the long-term reliability of the solar cell with metallization. 27 A moderately high temperature of 200…”
Section: Resultsmentioning
confidence: 99%
“…This depth difference increased to 65 nm after 5 minutes of annealing. While the top 70 nm was a ternary silicide alloy, Ni 45 Co 35 Si 20 in average, the bottom 65 nm layer had an average composition of Ni 60 Si 40 , or Ni 3 Si 2 . However, the double layered structure was not obvious in the cross sectional SEM in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental procedure was similar to the recent report by Bartsch et al 21 except that annealing at much lower temperatures for much longer time is included here. Light I-V measurements were conducted periodically to monitor the performance change of the cells.…”
Section: Figures 4a and 4b Show The 200mentioning
confidence: 99%
“…Since the Ag screen printed Si solar cells have been manufactured for decades, the standard tests for quality control have been well established, including UV irradiation, thermal cycling, damp heat test, and many others. 19,20 On the other hand, to our best knowledge, studies on the reliability of the Cu plated cells were not reported except for a recent report by Bartsch et al 21 In that study, they accelerated the cell degradation at elevated temperatures between 180 and 300…”
mentioning
confidence: 99%
See 1 more Smart Citation